2013
DOI: 10.1177/0886260512471085
|View full text |Cite
|
Sign up to set email alerts
|

Social Reactions to Disclosure of Sexual Victimization and Adjustment Among Survivors of Sexual Assault

Abstract: How a support provider responds to disclosure of sexual victimization has important implications for the process of recovery. The present study examines the associations between various positive and negative social reactions to sexual assault disclosure and psychological distress, coping behavior, social support, and self-esteem in a sample of college women (N = 374). Social reactions to assault disclosure that attempted to control the survivor's decisions were associated with increased symptoms of posttraumat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
160
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 175 publications
(179 citation statements)
references
References 45 publications
(58 reference statements)
9
160
0
4
Order By: Relevance
“…Maximizing the opportunities for a victim to perceive as much support as possible thus seems an important task for the members of the social network of a victim. Self-evident as this might seem, research has indicated that negative reactions from support network members like withdrawal and victim blaming are not uncommon (Orchowski et al, 2013;Silver, Wortman, & Crofton, 1990). In terms of policy implications, this finding suggests that as a part of the relief effort, victim support workers and organizations should try sensitizing (key) members of a victim's social network to this issue.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Maximizing the opportunities for a victim to perceive as much support as possible thus seems an important task for the members of the social network of a victim. Self-evident as this might seem, research has indicated that negative reactions from support network members like withdrawal and victim blaming are not uncommon (Orchowski et al, 2013;Silver, Wortman, & Crofton, 1990). In terms of policy implications, this finding suggests that as a part of the relief effort, victim support workers and organizations should try sensitizing (key) members of a victim's social network to this issue.…”
Section: Discussionmentioning
confidence: 96%
“…This typology is broadly accepted and has been used with research populations like students, battered women, and patients suffering from physical or mental disorders (e.g., Brissette, Scheier, & Carver, 2002;Cohen, Mermelstein, Kamarck, & Hoberman, 1985;Kaniasty & Norris, 1992). Because previous research has indicated that crime victims experience beneficial effects from having companions and being able to talk to others about their ordeal, from rebuilding self-esteem (Frieze & Bookwala, 1996) through supporting the seeking of emotional support (Orchowski et al, 2013), this typology is also highly relevant for victims of crime.…”
Section: Perceived Social Supportmentioning
confidence: 98%
See 1 more Smart Citation
“…While sexual assault is underreported to formal responders like the police, it is often disclosed to informal responders within social networks (Ahrens, Campbell, TernierThames, Wasco & Sefl, 2007;Fisher et al, 2003;Starzynski, Ullman, Filipas & Townsend, 2005). Survivors' choice of disclosure recipient can affect the type of response received (Ahrens & Aldana, 2012), which is associated with well-being (Orchowski et al, 2013;Ullman & Peter-Hagene, 2014), so understanding to whom survivors disclose is an important part of understanding their help-seeking experiences. However, this topic has been only minimally explored.…”
Section: Characteristics Of Social Networkmentioning
confidence: 99%
“…Survivors' choices regarding whether to seek help within their social networks and to whom of their available network members they disclose can have implications for the kinds of responses they receive (Ahrens & Aldana, 2012), which can, in turn, influence their continued help-seeking and well-being Orchowski, Untied & Gidycz, 2013;Ullman & PeterHagene, 2014). Thus, it is important to examine correlates of disclosure as part of identifying strategies to improve post-assault experiences.…”
Section: Introductionmentioning
confidence: 99%